The Use of Illocutionary Speech Acts in To Catch a Killer Movie (2023) - Cahyati, Firda Nur; Kuswahono, Deny; Setyowati, Yulis (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the types and prevalence of illocutionary speech acts in the film To Catch a Killer (2023), a psychological crime thriller rich in pragmatic nuances. The research aims to identify the categories of illocutionary speech acts used by characters and determine which type dominates the film’s dialogue. Employing a qualitative descriptive method, the researcher analyzed spoken utterances throughout the movie using Searle’s classification of illocutionary acts. Data were collected through systematic observation, transcription, and categorization of speech acts present in key scenes. The analysis reveals five types of illocutionary acts: assertive, directive, commissive, expressive, and declarative, with assertive acts being the most dominant (43%). These acts are crucial in conveying character intentions and advancing narrative tension. The findings contribute to pragmatic and linguistic studies by showcasing how illocutionary force is embedded within cinematic dialogue and how it reflects the psychological depth of storytelling. This study highlights the pedagogical value of film in teaching speech act theory and encourages further exploration of language in media contexts